2019
DOI: 10.1039/c9ra06143f
|View full text |Cite
|
Sign up to set email alerts
|

Rod-like anhydrous V2O5 assembled by tiny nanosheets as a high-performance cathode material for aqueous zinc-ion batteries

Abstract: V2O5 with intriguing micro/nano-hierarchical structure is fabricated via the pyrolysis of MIL-47 (a MOF material) and displays great performances as the cathode material for aqueous zinc-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Moreover, rod‐like anhydrous V 2 O 5 (RA‐V 2 O 5 , Figure 5b) assembled by tiny nanosheets also exhibits excellent performances, such as high reversible capacity (449.8 mA h g −1 at 0.1 A g −1 ), and great long‐term cyclability (86.8% of capacity retention after 2000 cycles at 2 A g −1 ), which are significantly superior to the control sample. [ 72 ] The reasons of such enhanced performance can be better explained from the aspect of morphology structure due to its larger specific surface (218 m 2 g −1 ) than control sample (5.3 m 2 g −1 ) and former's pore volume (0.96 cm 3 g −1 ) is larger than later (0.01 cm 3 g −1 ). Therefore, faster electrochemical kinetics and better performance can be achieved in RA‐V 2 O 5 /Zn battery.…”
Section: Challenges and Optimizationmentioning
confidence: 99%
“…Moreover, rod‐like anhydrous V 2 O 5 (RA‐V 2 O 5 , Figure 5b) assembled by tiny nanosheets also exhibits excellent performances, such as high reversible capacity (449.8 mA h g −1 at 0.1 A g −1 ), and great long‐term cyclability (86.8% of capacity retention after 2000 cycles at 2 A g −1 ), which are significantly superior to the control sample. [ 72 ] The reasons of such enhanced performance can be better explained from the aspect of morphology structure due to its larger specific surface (218 m 2 g −1 ) than control sample (5.3 m 2 g −1 ) and former's pore volume (0.96 cm 3 g −1 ) is larger than later (0.01 cm 3 g −1 ). Therefore, faster electrochemical kinetics and better performance can be achieved in RA‐V 2 O 5 /Zn battery.…”
Section: Challenges and Optimizationmentioning
confidence: 99%
“…Up to now, a variety of cathode materials for AZIBs have been reported, mainly including Mn-based oxides (Huang J. H. et al, 2018 ; Liu et al, 2019 ; Guo et al, 2020 ), V-based oxides (Tang F. J. et al, 2019 ; Zhou W. J. et al, 2019 ), Mo-based oxides (Kim et al, 2017 ), Prussian blue analogs (Trocoli and La Mantia, 2015 ), and organic and polymer compounds (Li B. Q. et al, 2018 ). Among them, MnO 2 might be the most promising one, primarily in terms of specific capacity and working potential (Ming et al, 2019 ; Zeng et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, such material can still delivers a specific capacity of 248 mAh g −1 even at a ultrahigh current density of 30 A g −1 , such outstanding rate capability should be mainly attributed to fast ions transport kinetics that boosted by the intercalation of H 2 O. [46,188] Another representative work was reported from Shin et al, [164] taking the mixed valence vanadium oxide, V 6 O 13 , as research object, they demonstrated that the hydrated intercalation can facilitates Zn 2+ diffusion pass through the electrodeelectrolyte interface and host lattice. To reveal the origin role of structural water in enhancing the electrochemical performance, they compared the kinetic behavior of Zn 2+ with and without water.…”
Section: H 2 O Intercalationmentioning
confidence: 99%
“…Furthermore, such material can still delivers a specific capacity of 248 mAh g −1 even at a ultrahigh current density of 30 A g −1 , such outstanding rate capability should be mainly attributed to fast ions transport kinetics that boosted by the intercalation of H 2 O. [ 46,188 ]…”
Section: Structural Engineering For Cathode Materialsmentioning
confidence: 99%